Clinical and psychological responses to synbiotic supplementation in obese or overweight adults: A randomized clinical trial. (December 2019) - Hadi, Amir; Sepandi, Mojtaba; Marx, Wolfgang; Moradi, Sajjad; Parastouei, Karim
Highlights: We examined the clinical and psychological responses to synbiotic supplementation in obese or overweight adults. Synbiotic supplementation can decrease body weight, TG, TC, LDL-c, stress, anxiety, and depression in overweight or obese adults. Supplementation with synbiotics did not affect the HDL-c, SBP, DBP, FBG and fasting insulin concentrations, as well the BMI and WC. Abstract: Background: Obesity is highly prevalent worldwide. Emerging clinical studies suggest that pre- and pro- biotic formulations may be effective interventions for the management of obesity and associated metabolic complications. The current trial was conducted to assess the effect of synbiotic supplementation on anthropometric indices, glycemic and lipid profile, blood pressure, and psychological status of adults with overweight or obesity. Methods: This randomized double-blind, placebo-controlled trial was conducted on 60 adults with overweight or obesity. Participants were randomly assigned into two groups to receive either synbiotics (n = 30) in form of a 500 mg capsule (containing Lactobacillus acidophilus, Lactobacillus casei and Bifidobacterium bifidum plus inulin) or placebo (n = 30) for 8 weeks. The level of total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), fasting blood glucose (FPG), insulin, body weight, body mass index (BMI), waist circumference (WC), systolic blood pressure (SBP), diastolic blood pressure (DBP), stress, anxiety, and depression were measured at the baseline and end of the study. Results: In total, 59 subjects (39 men and 20 women) completed the present study. A significant between-group decrease in body weight (P = 0.03), TC (P = 0.01), TG (P = 0.02), LDL-C (P = 0.01), stress (P < 0.001), anxiety (P = 0.03), and depression (P = 0.03) was found in the synbiotic group compared to the placebo. However, synbiotics had no significant effect on HDL-C, SBP, DBP, FPG and fasting insulin concentrations, as well the BMI and WC (P < 0.05). Conclusion: The present study showed that synbiotic supplementation can confer a number of health benefits including improvements in TG, TC, LDL-C, body weight, stress, anxiety, and depression to subjects that are overweight or obesity. Trial registration: Iranian Registry of Clinical Trials IRCT20180201038585N3.